The Feminist Utopia in Prema Shah and Rokeya S. Hossain: Linking the Real to the Ideal - Phuyal, Komal Prasad (SCHOLARS: Journal of Arts & Humanities, 2021)
Prema Shah’s “A Husband” and Rokeya S. Hossain’s “Sultana’s Dream” present two complementary versions of women’s world: the real in Shah and the imagined in Hossain aspire to make the other complete. The worldview that each author projects in their texts reasserts the latent spirit of the other one. The embedded interconnectedness between the authors under discussion reveals their unique association and bond of women’s creative unity towards paving a road for the upliftment of women in general. The paper seeks to find out the historical forces leading to the formation of a certain type of bond between these two authors from different historical and socio-cultural realities. Shah locates a typical Nepali woman in the protagonist in the patriarchal order while Hossain pictures the contemporary Bengali Islamic society and reverses the role of men and women. Hossain’s ideal world and Shah’s real world form two complementary versions of each other: despite opposite in nature, each world completes the other. Sultana moves to the world of dream to seek a new order because Nirmala’s world exercises every form of tortures upon the women’s self. Shah exposes the social reality dictating upon the women’s self while Hossain’s protagonist escapes into the world of dream where women control the social reality effectively and successfully. Overall, Shah and Hossain complement each other’s world by presenting two alternative versions of the same reality, creating the feminist utopia.